KETERAMPILAN SOSIAL SISWA KELAS V SDN 009 GUNUNG TOAR MELALUI PENERAPAN STRATEGI THINK TALK WRITE PADA MATA PELAJARAN SAINS - Yanto Yanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This study aims to describe the learning outcomes of students' social skills in science learning by applying the Think Talk Write (TTW) learning strategy to fifth grade students of the 009 state primary school in Mount Toar. The subjects of this study were the fifth grade students, amounting to 26 students. The instrument of data collection is a social skills observation sheet consisting of 5 attitude indicators. From the results of data analysis, an overview of the students' social skills is obtained, the indicators are in the task of taking turns in sharing tasks and listening actively are categorized as high, while the indicators encourage participation and ask are categorized as moderate. Overall the social skills of students are categorized as high which shows that the learning strategy of Think Talk Write effectively trains the social skills of public elementary school 009 Gunung Toar.